2017
DOI: 10.2214/ajr.16.17753
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Angiomyolipomas Among Echogenic Nonshadowing Renal Masses (> 4 mm) Found at Ultrasound and the Utility of MRI for Diagnosis

Abstract: Echogenic nonshadowing renal lesions larger than 4 mm seen at ultrasound should not be assumed to represent an AML without follow-up because a percentage of renal cell carcinomas will be missed. Although certain ultrasound features can be useful in differentiating an AML from a renal cell carcinoma and CT is frequently diagnostic, an understanding of MRI is important because it can potentially detect lipid-poor AMLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…This compares well to a 2017 study by De Silva et al who found a series of 158 hyperechoic masses in 132 patients with 62% confirmed AMLs. 17 The current lack of consensus regarding the surveillance of particularly subcentimetre echogenic renal lesions has led to various guidelines and recommendations. The present findings support previous studies that have demonstrated slow growth rates in small AMLs, and therefore, suggest that further follow-up is not required in the absence of symptoms or concerning imaging features.…”
Section: Discussionmentioning
confidence: 99%
“…This compares well to a 2017 study by De Silva et al who found a series of 158 hyperechoic masses in 132 patients with 62% confirmed AMLs. 17 The current lack of consensus regarding the surveillance of particularly subcentimetre echogenic renal lesions has led to various guidelines and recommendations. The present findings support previous studies that have demonstrated slow growth rates in small AMLs, and therefore, suggest that further follow-up is not required in the absence of symptoms or concerning imaging features.…”
Section: Discussionmentioning
confidence: 99%
“…One series found that 33 of 290 partial nephrectomies performed for a suspicious mass at CT yielded a diagnosis of an AML. 4,5 If an mpMRI had been performed in these cases and was strongly indicative of AML, those 10% could perhaps have avoided unnecessary major surgery.…”
Section: Resultsmentioning
confidence: 99%
“…This has significant clinical implications as lipid‐poor AMLs are difficult to diagnose radiologically on USS or CT, thus often leading to unnecessary surgical excision of an AML due to fears of it being an RCC. One series found that 33 of 290 partial nephrectomies performed for a suspicious mass at CT yielded a diagnosis of an AML 4,5 . If an mpMRI had been performed in these cases and was strongly indicative of AML, those 10% could perhaps have avoided unnecessary major surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations